Offengebliebene Fragen in der japanischen Kulturlandschaftsforschung für die Zeit von der Frühgeschichte bis heute - Schwind, Martin (ERDKUNDE, 1980)
This report deals with (1) problems of population and urban geography, (2) problems of agricultural geography, and (3) the Tokugawa regime in its geographical effectiveness. In part 1 stress is laid on the environmental behaviour of the governments in the Nara and Heian Periods by shifting the capital from Nara to Nagaoka and Kyoto, and prefering to build up provincial capitals at some distance from the coast, a behaviour that was inherited by the castle cities. Such cities, it is said, happened to be disadvantaged in the time of industrialisation as they lacked immediate connection with sea traffic. Correction of history is going on by constructing harbours for the castle-cities. The example is given of the development of Sendai. Finally, the problem of Yoshino, the capital at the time of Namboku-cho, is discussed. Part 2 deals with the governmental decree, given in 743, for rooting out woodland in order to enlarge the cultivated land. The effectiveness of this work on land scape is not yet well known. The same is the case with nimosaku and the problem of cattle feeding in former times and even today. In part 3 the Tokugawa Period is considered as a challenge for analysing the geographical effectiveness of a totalitarian state.